Penerapan Pendekatan Pembelajaran Sosial Emosional untuk Meningkatkan Kemampuan Menulis Teks Deskripsi pada Siswa Kelas V SDN Lio 1 Karangtengah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study is motivated by the low descriptive writing skills of elementary school students, which are influenced not only by linguistic aspects but also by students’ social and emotional conditions during the learning process. Writing instruction that remains teacher-centered and lacks emotional engagement often results in less meaningful learning experiences and low academic achievement. This study aims to improve the descriptive text writing skills of fifth-grade students at SDN Lio 1 Karangtengah through the implementation of a Social Emotional Learning approach. The research employed a quantitative approach using a Classroom Action Research design conducted in two cycles. The research subjects consisted of 25 fifth-grade students. Data were collected through classroom observations and descriptive writing tests, while data analysis was conducted quantitatively by examining improvements in students’ average scores, classical learning absorption, and learning mastery in each cycle. The results indicate a significant improvement in students’ descriptive writing skills from the first to the second cycle. The implementation of the Social Emotional Learning approach enhanced student engagement, improved the quality of students’ written work, and increased classical learning mastery. These findings suggest that integrating social and emotional aspects into Indonesian language instruction contributes to a more effective and meaningful learning process. The study implies that the Social Emotional Learning approach can serve as an alternative instructional strategy to support the holistic development of students’ writing skills at the elementary school level.